Simultaneous measure of companies' performance effectiveness and sustainability: A BOPSE indicator - Abreu, Maria Florentina Queirós Silva (2020)
The companies' performance effectiveness and sustainability, two imperative indicators of present-day business competitiveness, were partly and separately measured during many years. On one hand, the performance effectiveness has been measured through productivity, quality, cost, and other key performance indicators or a combination of them. On the other hand, many companies recognized the need to disclosure, and begun to measure, key environmental performance indicators. Nevertheless, few studies point out a global indicator that could simultaneously tackle both strands, which in turn would enable for a clearer assessment and endorsement of trade-offs among environmental and operational performances. This paper aims to present one such indicator, which measures the companies' lean-green compliance, by interweaving sustainability issues with those of the overall equipment effectiveness (OEE). The authors termed it Business Overall Performance and Sustainability Effectiveness (BOPSE) indicator. Its purpose relies on assessing the business effectiveness, based on both operational performance and sustainability compliance. While the performance effectiveness is appraised based on a well-established indicator, the authors felt the need to develop, adapt and simplify the particular indicators aiming the assessment of sustainability compliance. The later are mostly sourced, adapted and simplified from the Global Reporting Initiative (GRI). This development was contextualized in a Lean-Green environment; where continuous efforts to uncover and reduce all the Lean waste sources, plus the waste prevention perspective of cleaner production, environmental compliance and social responsiveness, play a major role in the development of the factories of the future. This paper provides a discussion on the development of the BOPSE model and a comparative analysis on the ones found on the literature, while providing insights into its relevance and wider application.